A mussel-inspired high bio-content thermosetting polyimine polymer with excellent adhesion, flame retardancy, room-temperature self-healing and diverse recyclability. Issue 21 (11th May 2022) - Zhao, Qi; Zhang, Meng; Gao, Shishuai; Pan, Zheng; Xue, Yijiao; Jia, Puyou; Bo, Caiying; Luo, Zhenyang; Song, Fei; Zhou, Yonghong
Abstract : A polyimine polymer with hydrogen bond–imine bond double dynamic cross-linked networks was synthesized by green methods using biomass feedstock. This study provides new and important insights into multifunctional polymers with high bio-based content. Abstract : Using renewable biomass instead of petrochemicals to prepare polymeric materials through green synthesis routes is one of the ways to achieve sustainability. In face of the ever-expanding practical applications, biomimicry is an effective approach to address the important challenges of realizing integrated functionalities in bio-based polymers. In this study, a polyimine polymer based on castor oil and vanillin prepared with simple green methods is reported, which combines fine mechanical properties, reprocessable high-efficiency adhesion, flame retardancy, room-temperature self-healing, and diverse recyclability. The structures imitating mussel adhesive protein endow the polymer with efficient adhesion on different substrates, among which the highest can reach 14.1 MPa on glass. The bottleneck of achieving high strength and high self-healing efficiency is overcome by introducing alternating rigid and flexible segments, active imine bonds, and abundant hydrogen bonds. Besides, the imine bond–hydrogen bond double dynamic network also gives the material characteristics of reprocessability and variable recyclability. The presence of aromatic rings, high nitrogen content and imine bonds greatly increases thermal stability and flame retardancy, with a V0 rating and LOI of 27.3%. Therefore, the material has great potential for use as a self-healing adhesive, and provides an excellent practical basis for the high functionalization and greening of polymeric materials.